2008
DOI: 10.1016/j.bmc.2008.06.030
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a butyrophenone analog as a potential atypical antipsychotic agent: 4-[4-(4-Chlorophenyl)-1,4-diazepan-1-yl]-1-(4-fluorophenyl)butan-1-one

Abstract: The synthesis and exploration of novel butyrophenones have led to the identification of a diazepane analogue of haloperidol, 4-[4-(4-chlorophenyl)-1,4-diazepan-1-yl]-1-(4-fluorophenyl)butan-1-one (compound 13) with an interesting multireceptor binding profile. Compound 13 was evaluated for its binding affinities at DA subtype receptors, 5HT subtype receptors, H-1, M-1 receptors and at NET, DAT, and SERT transporters. At each of these receptors, compound 13 was equipotent or better than several of the standards… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
48
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 46 publications
1
48
0
Order By: Relevance
“…1,5,4 Modifications of the piperidine ring resulting in D 2 receptor binding profiles that are similar or better than haloperidol and which could not form toxic pyridinium metabolites, were also identified. 4,6,7 These studies have indicated that adding an ethylene bridge to the piperidine moiety to form a tropane analog, maintained or increased affinity for the D 2 receptor subtype.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…1,5,4 Modifications of the piperidine ring resulting in D 2 receptor binding profiles that are similar or better than haloperidol and which could not form toxic pyridinium metabolites, were also identified. 4,6,7 These studies have indicated that adding an ethylene bridge to the piperidine moiety to form a tropane analog, maintained or increased affinity for the D 2 receptor subtype.…”
mentioning
confidence: 99%
“…5,9 Thus, it was of interest in this study, to further test the hypothesis that moderation of the binding affinity at the D 2 receptor could attenuate catalepsy in the tropane analogs of haloperidol. To test this hypothesis, we modified the fluorobutyrophenone moiety while replacing the piperidinol with 3-tropanol to obtain compounds 2-10 as shown in Fig 2 and then evaluated their binding affinities at receptors associated with antipsychotic activity, i.e., D 1 and D 2 -like receptors, 5-HT 1A R, 5-HT 2A R and 5-HT 7 R (Table 1).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous work indicated that pyridine and pyrimidine rings impacted binding to CNS receptors. 912 Hence, we first explored replacing the 4-chlorophenyl moiety with the pyridine ring in compounds 3–5 to obtain compounds 11–13 (Chart 2) and the binding affinities are reported in Table 2. Compounds 11–13 bind with very high affinities at D 4 versus D 1 –D 3 receptors, and therefore demonstrate decreased selectivity for the D 4 receptor.…”
Section: Resultsmentioning
confidence: 99%
“…1012 A frequent observation in such studies was the fact that unlike the piperidine analogs of haloperidol, the piperazine analogs demonstrated selective and significant affinities to the D 4 receptor subtype. Chart 1 displays common D 4 selective ligands with the piperazine pharmacophore.…”
Section: Introductionmentioning
confidence: 99%